Mental Health Insurance in India: An Examination of Policy Implementation Post-MHCA 2017 - Vijaya Chandra Reddy Avula; Sangha Mitra Godi; Shashidhara Munivenkatappa; Sridhar Amalakanti (Indian Journal of Psychological Medicine)
Purpose of review: Owing to the high cost of care and huge treatment gap associated with mental illnesses in India, this review investigated the implementation of mental health insurance coverage in India following the mandate of the Mental Health Care Act of 2017 (MHCA 2017). Collection and analysis of data: We systematically identified health insurance providers in India through the Insurance Regulatory and Development Authority of India (IRDAI) website. We meticulously searched and obtained policy documents from either the IRDAI website or the respective insurance company websites. Our classification process involved determining if a policy explicitly covered mental illness, which we discerned by examining definitions of mental illness, indemnification clauses or the presence of International Classification of Diseases-10 codes within the policy. Conclusion: We evaluated 235 policies provided by 30 insurance companies and found that 37.5% (88) of policies covered mental illnesses, 11.5% (28) covered persons with disabilities, whereas 51% (119) did not offer any coverage. The majority of the companies did not cover suicide and substance use disorders. There are disparities in the outpatient care offerings, including extended waiting periods for coverage of mental illness.  This review highlights the importance of aligning insurance practices with MHCA 2017s provisions to promote mental health equity in India. It also advocates for comprehensive mental health coverage that includes outpatient care, substance use disorders and suicide as well as a need for standardized definitions and transparent policy communication.